Pinnock, James (Jamaica : [Publisher not identified], 1748)
Diagram of lands in dispute, patented by James Pinnock, Elizabeth Read, and Isaac Allen. Submitted to the Court Feb. 22nd 1748 by R. Brown, Thomas Morphy and Mr. Rivers.
Keywords: Maps; St. Elizabeth (Jamaica) -- Maps